Optimized SFCL and SMES units for multimachine transient stabilization based on kinetic energy control - Ngamroo, Issarachai; Vachirasricirikul, Sitthidet (My University, 2013)
Power system transient instability due to short circuits may result in loss of synchronism. To improve stability, resistive type superconducting fault current limiter (SFCL) and superconducting magnetic energy storage (SMES) can be effectively used. This paper proposes a new optimization of multiple SFCL and SMES units for transient stabilization in a multimachine power system based on kinetic energy control. Two applications of the proposed optimization are studied in the West Japan six-area interconnected power system. First, the SFCL is applied to solve the inevitable problems of SMES used for transient stability enhancement, i.e., required large power and energy capacities, and fail-operational performance due to the large voltage drop at the SMES bus. When the fault occurs, the SFCL swiftly reduces the increase in the kinetic energy of all generators by limiting the fault current. Subsequently, the SMES handles the remaining unbalanced kinetic energy. The optimization problem of the resistive value of the SFCL is formulated, considering energy dissipation in combination with the power controller parameters of SMES with optimal coil size. A simulation study shows the superior effect of the combined SFCL and SMES over either device separately. With SFCL, the low voltage ride-through capability of SMES can be enhanced. The MW and MJ capacities of the SMES are also significantly reduced. Second, a new optimization of multiple SFCL units considering optimal locations, optimal number, optimal resistive values, and energy dissipation during quenching state is presented. The optimization problem is formulated by maximizing the decreasing rate of energy function during fault in combination with minimizing the energy dissipation of the SFCL during quenching state. A simulation study confirms the superior effect of optimal SFCL units over nonoptimal SFCL units. © 2002-2011 IEEE.
Keywords: Energy function; optimization; power system stability; superconducting fault current limiter; superconducting magnetic energy storage